A Case of Suspected Occupatinal Asthma in an Orthopedist, Due to Cast Materials Containing MDI - Komatsu, Takuzou; Miyamoto, Yasufumi; Muto, Hajime; Sano, Yasuyuki; Akiyama, Norihisa; Satoh, Fumihide; Tanaka, Yasuko; Arai, Yasuo (The Japanese journal of thoracic diseases, 1994)
A 38-year-old male presented complaining of an asthma attack. He had a past history of allergic rhinitis and conjunctivitis, family history of bronchial asthma and atopic dermatitis. He was an orthopedist who had been using cast materials containing methyelene diphenyl isocyanate (MDI) for one year, and had developed an early asthmatic response while handling the casts. An acetylcholine inhalation test was done and his value was 20000μg/ml. The scratch test for the cast materials was negative though the inhalation challenge test was positive. We suspected that the patient was suffering from bronchial asthma induced by MDI contained in the cast materials. Studies using isocyanates conjugated with human serum albumin were performed. The results were as follows: IgE-RAST negative, ELISA demonstrated the existence of specific IgG for both toluene diisocyanate (TDI) and MDI, as well as IgG4 for both TDI and MDI. The cast contained MDI but not TDI. We therefore considered TDI to be cross-reactant. It was likely that chronic exposure enhancing specific IgG4 and specific IgG might have caused the high IgG4 value. This is the first case report of occupational asthma in an orthopedist due to isocyanates.